Kinesiologic description of the round house kick: A brief review - Vieira Sarmet Moreira, P.; Vinhas de Paula, L. (Journal of Athletic Enhancement, 2017)
The Roundhouse kicks are the most used techniques to score in taekwondo competitions. However, the deeper understanding about the kinesiologic actions that occurs during the kick performance in this modality of sport is an arduous task, since there is no enough space in the published studies about this subject for the interpretation of the descriptive information. Consequently, there may be a low capacity for the full utilization of the knowledge obtained in these studies from those professional who work directly with this modality. Therefore, the goal of the present study is to perform an in-depth kinesiologic description of the taekwondo Roundhouse kicks. For this, we used the critical interpretation of some recent studies about the Roundhouse kick (Bandal Chagui). For didactic purposes, this technique was segmented into several phases and sub phases whose the mechanisms are sequentially associated. It was observed that the agonist muscle actions usually occur prior to their respective mechanical events, being attributed to the combination between two neuromechanical phenomena: electromechanical delay and motion-dependent-moment. It was interpreted that the antagonistic actions cause deleterious consequences to the velocity, but they have an important role for the joint stabilization. It was concluded that, in order to enhance the kick performance, maintaining the joint safety, athletes should train so that the peaks of activation, even those reflexes, of the antagonist muscles for the knee extension and for the hip flexion and adduction be postponed to the final part of the technique (i.e.:close to the impact moment).